2016
DOI: 10.1016/j.bjm.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Soil pretreatment and fast cell lysis for direct polymerase chain reaction from forest soils for terminal restriction fragment length polymorphism analysis of fungal communities

Abstract: Humic substances in soil DNA samples can influence the assessment of microbial diversity and community composition. Using multiple steps during or after cell lysis adds expenses, is time-consuming, and causes DNA loss. A pretreatment of soil samples and a single step DNA extraction may improve experimental results. In order to optimize a protocol for obtaining high purity DNA from soil microbiota, five prewashing agents were compared in terms of their efficiency and effectiveness in removing soil contaminants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Therefore, A 260/230 ratios obtained using commercial kits are lower than those obtained using our proposed method. Pre-treatment of soil with phenol:chloroform-guanidine thiocynate or Triton X-100-skim milk during the DNA extraction has shown the improvement in DNA quality (Antony-Babu et al, 2013;Cheng et al, 2016). However, the implementation of any of those steps increase the time effort, reagents, and cost of the extraction technique.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, A 260/230 ratios obtained using commercial kits are lower than those obtained using our proposed method. Pre-treatment of soil with phenol:chloroform-guanidine thiocynate or Triton X-100-skim milk during the DNA extraction has shown the improvement in DNA quality (Antony-Babu et al, 2013;Cheng et al, 2016). However, the implementation of any of those steps increase the time effort, reagents, and cost of the extraction technique.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the importance of purification in eliminating inhibitory substances from soil DNA samples is underscored [ 13 ]. Rapid DNA purification kits are available these days, but a significant portion of DNA is usually lost and DNA degradation or damage during the process is quite common during the process [ 48 ]. In our study as well, a decrease in DNA copy numbers was observed in purified samples compared to their respective crude samples, indicating a loss of DNA during the purification steps ( Figure 2 b).…”
Section: Discussionmentioning
confidence: 99%
“…Humic acid, originating from clay particles, is one of the most important contaminants as it may co-purify with DNA. To overcome this problem, a pre-washing step of soil with specific buffers efficiently removes contaminants [38], but with a risk of DNA loss. Nonfat skim milk is included in several DNA extraction protocols for its known ability to compete with DNA for adsorbing sites on clay particles, which results in more efficient DNA extraction [37,39].…”
Section: Dna Concentrations and Quality: Comparison Between Skmm And ...mentioning
confidence: 99%